Epidemiological Study in Admitted Patients With Ischaemic Heart Disease at a Tertiary Care Hospital in North-Western India - Singh, Arun; Mahawar, Dhirendra Kumar; Jain, Monica; Kapadia, Rupa; Dadhich, Jaya (Scripta Medica, 2023)
Background/Aim: Ischaemic heart disease (IHD) is a major cause of morbidity and the leading cause of mortality in either men or women globally. IHD incidence is more common in the elderly and there are multiple well-known risk factors for IHD. This study aimed to evaluate the epidemiological trend of IHD in North-Western India. This study also evaluated the risk factors of IHD and associated comorbidities.Methods: A cross-sectional observational study for a period of 12 months was conducted in the Cardiology Department of the Tertiary Care Hospital, Jaipur, India. A total of 400 IHD patients were enrolled in this study. Statistical Package for Social Sciences (SPSS) version 20.0 software was used for statistical calculation. Results: The most common age group was 61-80 years (Mean age was 57.8 ± 0.66) with men predominated (76.3 %). More patients (56 %) were from urban areas than rural areas (44 %). Among all the patients, 161 (40.3 %) patients were smokers and 42 (10.3 %) were alcoholics. Hypertension (34.8 %) followed by diabetes mellitus (17 %) and obesity (7.3 %) were found to be the predominant risk factors. Conclusion: IHD was more common in elderly patients and in men. Heavy alcohol consumption and smoking were potential risk factors for the development of IHD. Hypertension, diabetes mellitus and obesity also significantly contributed to occurrence of IHD. The burden of the IHD can be reduced by the limiting alcohol consumption, smoking cessation and adaptation of healthy lifestyle.
Keywords: Ischaemic heart disease; Risk factors; Epidemiology; Comorbidities